2008
DOI: 10.1177/1049732308323840
|View full text |Cite
|
Sign up to set email alerts
|

“I am not a robot!” Interpreters' Views of Their Roles in Health Care Settings

Abstract: In this study, I examined interpreters' self-perceived roles and their corresponding communicative goals and strategies. Twenty-six professional interpreters (of 17 languages), 4 patients, and 12 health care providers were recruited for this study, which involved participant observation of medical encounters and in-depth interviews. Constant comparative analysis was used to generate a typology of interpreters' self-perceived roles, which are different from the roles they learned in their training. Different ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 25 publications
9
103
0
4
Order By: Relevance
“…[10][11][12] Although patient advocate is an official role that professional interpreters learn during their training, many refrain from advocacy behaviors due to concerns about institutional hierarchy or job security. 13,14 Bilingual staff interpreters have the advantage of familiarity with clinicspecific knowledge; however, they may not have sufficient linguistic skills for interpreting tasks and feel overwhelmed with other responsibilities. 15,16 Compared to professional onsite interpreters, remote interpreters (e.g., telephone and videoconferencing interpreters) are more cost-effective, accessible, and equally accurate.…”
mentioning
confidence: 99%
“…[10][11][12] Although patient advocate is an official role that professional interpreters learn during their training, many refrain from advocacy behaviors due to concerns about institutional hierarchy or job security. 13,14 Bilingual staff interpreters have the advantage of familiarity with clinicspecific knowledge; however, they may not have sufficient linguistic skills for interpreting tasks and feel overwhelmed with other responsibilities. 15,16 Compared to professional onsite interpreters, remote interpreters (e.g., telephone and videoconferencing interpreters) are more cost-effective, accessible, and equally accurate.…”
mentioning
confidence: 99%
“…The California Healthcare Foundation has recently developed a free online curriculum for interpreters in palliative care. 22 Our study had several limitations. To target the largest number of interpreters, we used a national convenience sample.…”
Section: Discussionmentioning
confidence: 91%
“…The role of the interpreter can also be extended to a role as mediator and a bridge between cultures (Rosenberg et al 2008;Messias et al 2009). Professionals state that the alliance of providers and interpreter also supports the patient's emotional needs (Hsieh & Hong 2010) and the interpreter's behaviour and the alliance between providers and interpreter are critical to the success of the interpreting situation (Hsieh 2008;Krupic et al 2016).…”
Section: Language Interpreting Practices In Healthcarementioning
confidence: 99%
“…There have also been studies identifying problems when using interpreter in healthcare (Hadziabdic et al 2011;Krupic et al 2016) and investigating factors influencing the provider's choice of interpreter (Hsieh 2015). Studies have been found regarding the interpreter's role and behaviour during healthcare encounters (Leanza 2005;Hsieh 2008;Hsieh & Kramer 2012;Hadziabdic & Hjelm 2016).…”
Section: Introductionmentioning
confidence: 99%